Sistemas de produção de porta-enxertos de seringueira - Guiducci, Erika Perches [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Rubber trees are propagated by grafting method and its seeds used for obtaining the rootstocks. Environmental problems related to rootstocks development by the conventional system and the establishment of rules (Resolução SAA - 154/2013 of the São Paulo State) for production in suspended nurseries have motivated researches of new processes for rubber rootstocks production. The objective of this study was to evaluate rubber rootstocks production in suspended containers in a greenhouse and open skies. An experiment of seeding and another of development of rootstocks were conducted in Tanabi – SP/Brazil. The experiment of seeding compared the germination and vigor of rubber seeds among different seeding systems: conventional in soil beds, direct seeding on substrate in suspended containers in a greenhouse and at open skies. Emergence speed index and percentage of germination of seeds were evaluated in each seeding system. The results showed that the direct seeding system in the greenhouse is the most suitable for providing better seeds germination and adaptation to legislation, and that it is essential to use high vigor seeds. The experiment of development of rubber rootstocks evaluated the conventional production system under field conditions compared to greenhouse and open skies suspended containers systems. Diameter at five cm from colon, height, leaf area, root volume and dry weight of shoot and root system of the rootstocks were evaluated. It was concluded that, in the São Paulo Western Plateau region, the production of rubber rootstocks should be conducted in the greenhouse suspended containers system using an organic substrate

A seringueira é propagada vegetativamente pelo método da enxertia e suas sementes usadas para a obtenção dos porta-enxertos. Problemas ambientais relacionados ao desenvolvimento das plantas pelo sistema convencional e o estabelecimento de normas (Resolução SAA – 154/2013 do Estado de São Paulo) para a formação de mudas têm motivado estudos de novos processos para formação de porta-enxertos. O objetivo deste trabalho foi avaliar a produção suspensa de porta-enxertos de seringueira em ambiente protegido e a céu aberto. Foi realizado um experimento de semeadura e um de desenvolvimento de portaenxertos no município de Tanabi – SP. Comparou-se a germinação e o vigor de sementes de seringueira entre diferentes sistemas de semeadura: convencional em canteiros de germinação e direta em substrato sobre bancada protegida e a céu aberto. Foram avaliados o índice de velocidade de emergência e a porcentagem de germinação das sementes em cada sistema de semeadura. Os resultados obtidos nas condições experimentais permitiram concluir que o sistema de semeadura direta em substrato em ambiente protegido é o mais indicado por proporcionar melhor germinação das sementes e adequação à legislação, e que é fundamental a utilização de sementes com alto vigor. O experimento de desenvolvimento de portaenxertos avaliou o sistema de produção de mudas convencional nas condições de campo em comparação com o sistema suspenso em bancada, em ambiente protegido e a céu aberto. Foram avaliados o diâmetro a cinco cm do colo, a altura, a área foliar, o volume de raiz e a matéria seca da parte aérea e do sistema radicular das plantas. Concluiu-se que, na região do planalto ocidental paulista, a produção de porta-enxertos de seringueira deve ser conduzida em sistema de bancada protegida e com uso de substrato orgânico
Keywords: Seringueira; Porta-enxertos; Plantas - Propagação; Viveiros de mudas; Germinação; Rubber plants